Аналіз доступності вокзалів АТ «Українська залізниця» для людей з обмеженими можливостями - Музикін, Михайло Ігорович; Нестеренко, Галина Іванівна; Авраменко, Світлана Ігорівна (Східноукраїнський національний університет ім. В. Даля, Луганск, 2019)
UKR: У даній статті розглянуте питання проблем перевезення людей з обмеженими можливостями. Проведено аналіз доступності вокзалів Дніпро, Запоріжжя-1, Львів, Чернівці та Чоп для людей з обмеженими можливостями. Надані рекомендації щодо безперешкодного доступу до вокзалів для маломобільних пасажирів. Створити всі умови для того, щоб люди з обмеженими фізичними можливостями відчували себе вільно і впевнено – саме в цьому полягає завдання держави в сфері соціального захисту населення.

ENG: In this article the question of problems of transportation of physically disabled people is considered. The analysis of availa-bility of stations Dnipro, Zaporizhia-1, Lviv, Chernivtsi and Chop for physically disabled people is carried out. Recommendations for unimpeded access to stations for handicapped passengers are given. To create all conditions in order that physically disabled people felt freely and surely – this is the task of the state in the sphere of social protection of the population consists. To date, JSC "Ukrainian Railways" is carrying out a great deal of work on the gradual incorporation into the trains of long-distance trains of specialized cars for the transportation of persons with disabilities. In addition, necessary conditions are created for the safe use of persons with disabilities in the transport infrastructure: railway stations, railway stations, railways crossings, etc.

RUS: В данной статье рассмотрен вопрос проблем перевозки людей с ограниченными возможностями. Проведен анализ доступности вокзалов Днепр, Запорожье-1, Львов, Черновцы и Чоп для людей с ограниченными возможностями. Даны рекомендации по беспрепятственному доступа к вокзалам для маломобильных пассажиров. Создать все условия для того, чтобы люди с ограниченными физическими возможностями чувствовали себя свободно и уверенно – именно в этом состоит задача государства в сфере социальной защиты населения.
Analysis of the Availability of the Station of JSC «Ukrainian Railway» for People with Disabilities
Анализ доступности вокзалов АО «Украинские железные дороги» для людей с ограниченными возможностями
Г. Нестеренко: ORCID 0000-0003-1629-0201; М. Музикін: ORCID 0000-0003-2938-7061; С. Авраменко: ORCID 0000-0002-5832-6949
Keywords: особа з обмеженими можливостями; маломобільні пасажири; вокзал; безперешкодний доступ; a person with disabilities; handicapped passengers; railway station; unhindered access; лицо с ограниченными возможностями; маломобильные пассажиры; беспрепятственный доступ; КУЕР; КБЖД; КІТ